MOLECULAR DYNAMICS SIMULATIONS: EXPLORING THE TEMPORAL EVOLUTION OF COMPLEX SYSTEMS FOR THERMODYNAMIC AND BIOLOGICAL INSIGHTS (International Journal of Food and Nutritional Sciences, 2022)
Molecular dynamics (MD) simulations offer a powerful computational approach to track the precise temporal evolution of systems under defined conditions, such as specific temperature or pressure. By leveraging statistical mechanics, these simulations provide comprehensive insights into thermodynamic properties and dynamic behaviors. Beyond thermodynamics, MD simulations enable detailed exploration of chemical reaction mechanisms and other time-dependent processes, including diffusion. Particularly, in the context of biomaterials, MD simulations facilitate a deeper understanding of structure-activity relationships and aid in the rationalization of biological applications, making them an indispensable tool in the study of complex and extensive systems.